Wood-Reinforced Polymer Composites - Akdogan, Anil; Vanli, Ali Serdar (INTECH EUROPE, 2017)
The importance of protection of natural resources, recycling and biodegrability are the basic reasons behind the increased use of lignocellulosic (LC) material-reinforced polymer composites. This chapter investigates wood filler-reinforced polymer composites, which have gained attention among the researchers and in the market in woody applications having aesthetic and low service costs. Most polymers have the increasing cost of petrochemical products while LC materials are obtained from different national resources such as different types of wood powder. LC materials are available in light, cheap, environment-friendly forms with easy maintenance. The main disadvantages of LC-reinforced composites are moisture sensitivity and poor dimensional stability, besides changing wood fiber characteristics in time and poor adhesion to basically all kind of matrix polymers. Additive usage in manufacturing is an increasing trend of wood-based LC material-reinforced polymer composite parts to penetrate new markets, with better performance requirements and long-term stability. This chapter investigates description, classification, production with common additive types and usage of wood-polymer composite materials. In addition, it approaches preprocesses to reach high productivity and high-quality product manufacturing. Finally, some experimental manufacturing results of wood-reinforced polymer composites are presented.
Keywords: polymer composites; wood reinforcements; lignocellulosic materials; manufacturing methods; product quality; PLASTIC COMPOSITES; MECHANICAL-PROPERTIES; PP COMPOSITES; FIBER COMPOSITES; FLOUR; EXTRUSION; AGENT; MORPHOLOGY; ADHESION; MOISTURE; Construction & Building Technology; Engineering; Materials Science